2007
DOI: 10.1002/term.55
|View full text |Cite
|
Sign up to set email alerts
|

In vivo imaging and evaluation of different biomatrices for improvement of stem cell survival

Abstract: Therapeutic effects from injection of stem cells are often hampered by acute donor cell death as well as migration away from damaged areas. This is likely due to the fact that injected cells do not have the physical and biochemical cues for ordered engrafment. Here we evaluate 3 common biomatrices (Matrigel, Collagen I, Purmatrix) that has the potential of providing suitable scaffolds needed to enhance stem cell survival. The longitudinal fate of transplanted stem cells was monitored by reporter imaging techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 11 publications
0
28
0
1
Order By: Relevance
“…In addition, the shear-thinning, injectability, and self-healing properties of the MITCH materials make them attractive candidates for potential cell injection applications. Currently, we are using a dorsal subcutaneous mouse model (16) to monitor the viability and distribution of cells delivered via injection within MITCH materials.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, the shear-thinning, injectability, and self-healing properties of the MITCH materials make them attractive candidates for potential cell injection applications. Currently, we are using a dorsal subcutaneous mouse model (16) to monitor the viability and distribution of cells delivered via injection within MITCH materials.…”
Section: Discussionmentioning
confidence: 99%
“…Matrigel is a commercially available hydrogel commonly used for cell encapsulation and transplantation preclinical studies. However, because of its isolation from the basement membrane of a mouse sarcoma, Matrigel is unlikely to be approved for clinical use (16,17). These data demonstrate that the viscoelastic properties exhibited by the MITCH materials are within the appropriate range for cell encapsulation and transplantation applications.…”
Section: Microrheology and Bulk Rheology Of Protein-engineered Hydrogmentioning
confidence: 96%
See 2 more Smart Citations
“…When injected along with human embryonic stem cell-derived cardiomyocytes into infarcted hearts of rats, matrigel substantially increased stem cell engraftment and survival in a recent study (45), suggesting that matrigel forms a scaffold capable of reducing the apoptosis (anoikis) induced by the need to detach anchorage-dependent cells from their surrounding matrix before intramyocardial injection. Using noninvasive longitudinal bioluminescence imaging, authors of another recent study (46) have shown that matrigel significantly increases long-term survival (up to 5 months) of bone marrow-derived mesenchymal stem cells injected subcutaneously into mice compared with other biomatrices, such as type 1 collagen and puramatrix, or with PBS only. Our results are in line with those of these studies.…”
Section: Molecular Imaging: Imaging Gene Expression In Human Mesenchymentioning
confidence: 99%